Islamic Law in Western Scholarship: A Bilbiographical Study with Emphasis on the Work of Joseph Schacht and Its Influence on His Successor - Akh. Minhaji (Al-Jami'ah: Journal of Islamic Studies, 1993)
It should be important first of all to throw some light upon western scholar’s understanding of the doctrine of Islamic law and its important position among Muslim societies, particularly as compared to that of natural law. Law in any society play a decisive role. The primary purpose of any law is to make social life possible. Law, according to some scholars, “is the legal norm approved by people, and derives its authority form the reason and will of man, and his moral nature. “Law reflects the values current in a society at any given time. The society has its starting point in the formulation of a legal code for its acts and activities. Opinions regarding legal or illegal acts and activities change, sometime diametrically, as values change. When this situation takes place, the law is altered accordingly. The Muslim conception about law is quite different. According to the classical theory, Allah is the only source of Islamic law is the will of Allah, revealed in the Qur’an to humankind through His Messenger, Muhammad, and it is regarded as “a divinely ordained system preceding and not preceded, controlling and not controlled by Muslim society. “Therefore, the doctrine that Allah possesses all legislative power and that His law to have supreme control over all aspects of human life is clearly established.